“Role of hematological parameters as an indicator of acute malarial infection in Uttarakhand state of India” - Smita Chandra; Harish Chandra (Mediterranean Journal of Hematology and Infectious Diseases)
Background Malaria may be associated with complications which may be avoided by early diagnosis and treatment. Microscopic diagnosis showing presence of malarial parasites is needed for confirmation which at times may be unreliable and requires technical expertise. The present study was conducted to statistically analyze the haematological parameters including platelet indices which can give initial hint for malarial infection and therefore prompt the laboratory physician for active search of the parasite microscopically. Methods A retrospective study was conducted which included 334 cases of acute malaria caused by Plasmodium vivax, falciparum and dual infection along with 100 cases of control. Routine haematological parameters along with platelet indices (MPV and PDW) which are easily available on automated cell counter were statistically analyzed to assess their role as indicators for malaria. Results Leukocyte count and platelet count were significantly lower in cases of acute malaria in comparison to controls (p value <0.001). Platelet count<150x109/l showed 87.2% sensitivity, 65% specificity, 89.3% positive predictive value and 2.49 likelihood ratio for the infection. PDW of 6-10 and MPV>8 fl had 71.9% and 61.5% sensitivity and 78.2% and 77.7% positive predictive value respectively for infection. Platelet count <150x109/l and MPV>8 fl was comparatively more sensitive indicator for vivax (88% and 70.8% respectively) than falciparum (84.8% and 50.4% respectively) and PDW 6-10 was more sensitive indicator for falciparum (82.6%) than vivax (69.5%) infection. Conclusion Thrombocytopenia (<150x109/l) and low leukocyte count (<4x109/l) may be used as probable indicator for malaria. Higher MPV (>8 fl) and PDW of 6-10 also show considerable sensitivity for malarial infection. In addition, thrombocytopenia (<150x109/l) and higher MPV (>8 fl) was more sensitive for vivax infection while PDW 6-10 was more sensitive for falciparum infection.